“I’m living in a ‘no’ world now…”- A qualitative study of the widespread impact of living with chronic breathlessness, and experiences of identification and assessment of this symptom in an older, frail community-based population - Helene L. Elliott-Button; Miriam J. Johnson; Ann Hutchinson; David C. Currow; Joseph Clark (npj Primary Care Respiratory Medicine)
Abstract Chronic breathlessness is a debilitating symptom with detrimental impact on individuals and carers. However, little is known about the experiences of community-dwelling, frail, older adults living with chronic breathlessness. To explore, (i) the psychological impact of living with chronic breathlessness, (older frail adult patients, carers) and (ii) how patients, carers, and clinicians experience identification and assessment of chronic breathlessness in the primary care setting. In-depth semi-structured interviews with eligible older adults (≥65 years; moderate to severe frailty [electronic Frailty Index >0.36]), and carers recruited from a community-based Integrated Care Centre in England. Clinicians were recruited from the Centre and affiliated GP practices. Recorded in-person interviews were transcribed and subjected to reflexive thematic analysis using Total Dyspnoea and Breathing Space conceptual frameworks. 20 patients (9 females), carers (4 spouses, 1 daughter), and clinicians (5 GPs, 3 advanced clinical practitioners, 2 nurses) were interviewed. Four themes were identified: (1) Widespread negative impact of chronic breathlessness. Breathlessness adversely impacts physical and psychological wellbeing. (2) Barriers to optimal health-seeking and identification of chronic breathlessness. Breathlessness is ‘one of many’ symptoms, and not prioritised in ‘one appointment, one problem’ consultations. Clinicians do not routinely ask about breathlessness. Patients are unaware of breathlessness-specific therapies. (3) Variations in chronic breathlessness management. Management is limited; few are offered evidence-based treatments (e.g., handheld fan) and patients find their own strategies. (4) Need for education and information. Clinicians felt helpless about breathlessness management, and patients lacked understanding and had low expectations of receiving help for this symptom. Breathlessness adversely impacts the psychological wellbeing of older frail adults. Chronic breathlessness in older, frail adults is invisible, unidentified and unmanaged in primary care. Evidence-based breathlessness interventions are available, but not routinely implemented with few patients accessing them. Proactive identification, assessment and management of breathlessness in primary care is needed to support adults living with chronic breathlessness.